Effect of Vitamin D supplementation to reduce respiratory infections in children and adolescents in Vietnam: A randomized controlled trial. Issue 2 (4th January 2019) - Loeb, Mark; Dang, Anh Duc; Thiem, Vu Dinh; Thanabalan, Vitheya; Wang, Biao; Nguyen, Nguyen Binh; Tran, Hung Thi Mai; Luong, Tan Minh; Singh, Pardeep; Smieja, Marek; Maguire, Jonathon; Pullenayegum, Eleanor
Abstract : Background: It is uncertain whether vitamin D can reduce respiratory infection. Objective: To determine whether vitamin D supplementation reduces influenza and other upper viral respiratory tract infections. Methods: A total of 1300 healthy children and adolescents between the ages of 3 and 17 years were randomized to vitamin D (14 000 U weekly) or placebo for 8 months in Vietnam. The primary outcome was reverse transcriptase (RT)‐PCR–confirmed influenza infection, and the coprimary outcome was multiplex PCR–confirmed non‐influenza respiratory viruses. Participants, caregivers, and those assessing outcomes were blinded to group assignment. Results: A total of 650 children and adolescents were randomly assigned to vitamin D and 650 to placebo. The mean baseline serum 25‐hydroxyvitamin D levels were 65.7 nmol/L and 65.2 nmol/L in the intervention and placebo groups, respectively, with an increase to 91.8 nmol/L in the vitamin D group and no increase, 64.5 nmol/L, in the placebo group. All 1300 participants randomized contributed to the analysis. We observed RT‐PCR–confirmed influenza A or B occurred in 50 children (7.7%) in the vitamin D group and in 43 (6.6%) in the placebo group (hazard ratio [HR]: 1.18, 95% CI: 0.79‐1.78). RT‐PCR–confirmed non‐influenza respiratory virus infection occurred in 146 (22.5%) in the vitamin D group and in 185 (28.5%) in the placebo group (hazard ratio [HR]: 0.76, 95% CI: 0.61‐0.94). When considering all respiratory viruses, including influenza, the effect of vitamin D in reducing infection was significant, HR: 0.81, 95% CI: 0.66‐0.99. Conclusion: Vitamin D supplementation did not reduce the incidence of influenza but moderately reduced non‐influenza respiratory viral infection.